Design and Implementation of Home Industrial-Based Automatic Granulated Food Weighing Machine - Mia Galina (JURNAL INFOTEL, 2024)
Automation activities are now required in manufacturing processes. This process can provide very effective and efficient performance results, particularly for industrial processes that require a specific standard, such as those used in the granulated food product industry, such as sugar, rice, coffee, and other products. Fast, sanitary packaging processes and standard weights are the main focus of the manufacturing process. This is not a significant barrier at the level of an established industry, whereas, in traditional processes, this is still the main impediment since automated weighing systems at reasonable prices are still challenging to come by in small and medium-sized businesses. This study proposes the development of a prototype weighing mode that can maintain the weight accuracy of powder materials (sugar, rice, and coffee) before they are placed in product packaging. The research employed the experimental method, utilizing a load cell sensor and a screw conveyor to precisely measure the weight of powder raw materials based on the user-specified size and parameters. It is also equipped with a data deviation memory. Some testing was conducted to ensure the accuracy of the prototype. Based on the test results, this system can work with an accuracy rate of 99.693% at parameters 120 grams and 99.677% when testing the weight of powder raw materials of 120 grams, 125 grams, and 175 grams, respectively.